Molecular predictive factors of outcome of radiotherapy in cervical cancer - Petera, J; Sirak, I; Beranek, M; Vosmik, M; Drastikova, M; Paulikova, S; Soumarova, R (Neoplasma, 2011)
Radical radiotherapy with concurrent cisplatin-based chemotherapy is an established treatment for cervical cancer patients with stage FIGO IIB and higher. The tumor control can be achieved in 40-80% of patients, the treatment is associated with the risk of late postiradiation complications in 10 - 15% of cases. Detection of the factors predictive for tumor control and late morbidity is a possible direction how to individualize radiotherapy dose and technique. The aim of our review is to summarize results of studies inquiring various molecular markers predicting tumor response to radiotherapy and a risk of late complications. A lot of candidate molecules were evaluated in histochemical studies: membrane receptors (EGFR, HER-2), cell cycle regulators (p53, p21), proliferative markers (Ki-67), hypoxia and angiogenetic factors (HIF, VEGF), HPV status, and others (COX-2), with promising results in some of them (HPV, HIF-1α, Ku80, ATM polymorphism). Microarray studies identified decades of genes with different expression in radiosensitive/radioresistant cervical tumors and sets of genes are able to comletely separate responding and nonresponding tumors, but these sets differ across studies. Further well designed studies will be necessary to achieve results matured for use in clinical practice.
Keywords: Biomarkers, Tumor; Uterine Cervical Neoplasms; nádorové biomarkery; Female; nádory děložního čípku; Humans; ženské pohlaví; lidé